Sistem Rekrutmen Tenaga Pendidik Di Madrasah Swasta - Zakiyah Kholidah (Al Hikmah: Jurnal Studi Keislaman, 2018)
Abstract, the dynamics of the state of human resources working within the madrasafrom time to time continue to change. Madrasah educator resources can work for along time and some only last a few years. Many reasons behind it are those who getnew assignments in other places, move areas because of family factors, and can alsobecause they have to resign for the recovery of their health. Of course, suchconditions in the madrasa occur when there is a vacant position that must find areplacement. Employment in the madrasa becomes a necessity for recruitment byconsidering the need for additional human resources in the madrasa. Throughrecruitment activities, a search process can be carried out, getting prospectiveapplicants, selecting and placing new selected educators who have the ability andexpertise as required to fill the vacancy in the madrasa. The recruitment process inmany madrasas is not carried out by the steps according to the management functionbut there are many practices using roads that are not in accordance with the conceptof implementing recruitment. From an ineffective way of making madrassas get neweducators who do not meet the criteria needed by madrasas. New educators who donot have expertise result in low work motivation and madrasa performance is alsodifficult to increase. Recruitment practices through nepotism, appointment of youngworkers who do not have experience, appointment due to pity factors often occur byprivate madrasas. The practice is in the view of the community that madrasas have noattempt to seriously improve the performance of madrasas to assist students inlearning science and the formation of noble character. Keywords: recruitment, educators, private madrassas